Directing Mesenchymal Stem Cells with Gold Nanowire Arrays. Issue 14 (10th May 2018) - Zhou, Qihui; Zhao, Zhiyuan; Zhou, Ziwei; Zhang, Gang; Chiechi, Ryan C.; van Rijn, Patrick
Abstract: Controlling cell organization is still a major bottleneck in biointerface engineering when the material dimensions decrease to the nanoscale. Here, Au nanowire‐patterned array platforms with multiscale design from the macroscale to the nanoscale are developed for studying human bone marrow–derived mesenchymal stem cell (hBM‐MSC) response. When the angle of the Au nanowires on glass is increased from 0° to 90°, hBM‐MSC arrangement exhibits a transition from a unidirectional distribution induced by a vector response to a bimodal polarization pattern. The degree of cell vector response and elongation decreases with increasing nanowire angles from 0° to 90°. Further, it is demonstrated that the specific cell adhesion and organization are dependent on the surface micro/nanotopography, which is greatly enhanced by introducing stem cell‐material affinity differences. An ideal model and new insights into a deeper understanding of cell–nano‐biointerface interactions are provided. Abstract : The novel nano‐biointerface platforms with control over size, spacing, pattern, and chemical cues are developed using the nanoskiving technology. Precise control over cell morphology and organization, especially the vector alignment of cells, is achieved using the synergistic effects of gold nanowire‐arrays and stem cell‐material affinity differences as driving forces for stimulating cells at nano‐, micro‐, and macroscopic dimensions.